Pengaruh Harga Jual Nikel dan Produksi Nikel Matte Terhadap Nilai Saham PT Vale Indonesia Tbk Studi Kasus Bursa Efek Indonesia - Ryan Irfansyah; Hasni Kasim; Hendra Sani (Fakultas Teknik UPRI, 2026)
This study aims to analyze the effect of nickel selling price and nickel matte production on the stock value of PT Vale Indonesia Tbk listed on the Indonesia Stock Exchange during the 2020–2024 period. The data used are secondary data consisting of global nickel prices, nickel matte production volume, and PT Vale stock prices obtained from company annual reports and market publications. The analytical methods applied are simple linear regression and Pearson correlation tests. The results indicate that the nickel selling price significantly affected the stock value in 2020, 2021, and 2023 with a very strong correlation (r > 0.90), while in 2022 and 2024 the effect was not significant. On the other hand, nickel matte production did not significantly influence the stock value during the research period, showing weak correlation values. This study concludes that global nickel prices are the dominant fundamental factor influencing PT Vale’s stock movement, while nickel matte production is not a primary determinant for investors.